Tradisi Tahlilan Masyarakat Jawa: Studi Tinjauan Pustaka tentang Nilai Dasar Kemanusiaan dalam Perspektif Schwartz - Lynda Yenie Listaunsanti; Listyo Yuwanto (Medan Resource Center, 2025)
This study examines the meanings embedded in the Javanese tahlilan tradition through the lens of Schwartz’s basic human values, focusing on benevolence, tradition, conformity, and social security. The research addresses how these values are articulated within tahlilan as a form of local Islamic practice and their significance for social cohesion in Javanese Muslim communities. Employing a literature review approach, this study analyzes scholarly works published over the last decade, selected based on thematic relevance to ritual practices, Islamic local wisdom, and value theory, and examined using qualitative content analysis. The findings indicate that tahlilan functions as a cultural-religious mechanism that reinforces altruistic social relations, preserves inherited ritual traditions, regulates communal behavior through shared norms, and fosters emotional as well as social stability. Collectively, these values position tahlilan not merely as a ritual practice but as a meaningful expression of humanity-centered ethics within Javanese Islam, demonstrating the analytical relevance of Schwartz’s theoretical framework for understanding local religious traditions.